A computational study of the temperature dependence of interface and surface energies in WC–Co cemented carbides. (February 2020) - Gren, Martin A.; Fransson, Erik; Wahnström, Göran
Abstract: Interfaces and surfaces often play a vital role for the properties of polycrystalline materials, such as cemented carbides, and the study of these planar defects is, therefore, of great importance. Cemented carbides (or hardmetals) is a unique class of materials where hard carbide (WC) grains, usually micrometer sized, are embedded in a more ductile metal binder phase (usually Co) in order to combine superb strength with high hardness, making them ideal as tool material in e.g. metal machining. In the manufacturing and industrial usage of cemented carbides temperatures reach high levels, especially in the former case where the material is sintered at temperatures where the binder phase is a liquid. This is a computational study of the temperature dependence of interface and surface energies in WC–Co cemented carbides upto and above the melting temperature of Co. We make use of an analytical bond order potential (ABOP) fitted to density functional theory (DFT) data in order to make the free energy calculations feasible. A variety of free energy methods are used: including quasi harmonic approximation, temperature and thermodynamic integration, and calculation of liquid surface tension and work of adhesion for phase boundaries. We present the temperature dependent interface and surface energies for some typical cases, data which should be useful as a supplement to other studies limited to 0 K. Highlights: Temperature dependent interface and surface energies in WC-Co cemented carbides. Computational investigation using an analytical bond order potential (ABOP). Quasi harmonic approximation, λ-integration and temperature integration for solids. Surface stress/tension for liquid Co surface. Simulations of work of adhesion for WC/Co phase boundaries.